Characterization of Candidate Live Oral Salmonella typhi Vaccine Strains Harboring Defined Mutations in aroA, aroC, and htrA - Lowe, David C. (American Society for Microbiology, 1999)
The properties of two candidate Salmonella typhi-based live oral typhoid vaccine strains, BRD691 (S. typhi Ty2 harboring mutations in aroA and aroC) and BRD1116 (S. typhi Ty2 harboring mutations in aroA, aroC, and htrA), were compared in a number of in vitro and in vivo assays. BRD1116 exhibited an increased susceptibility to oxidative stress compared with BRD691, but both strains were equally resistant to heat shock. Both strains showed a similar ability to invade Caco-2 and HT-29 epithelial cells and U937 macrophage-like cells, but BRD1116 was less efficient at surviving in epithelial cells than BRD691. BRD1116 and BRD691 were equally susceptible to intracellular killing within U937 cells. Similar findings were demonstrated in vivo, with BRD1116 being less able to survive and translocate to secondary sites of infection when inoculated into the lumen of human intestinal xenografts in SCID mice. However, translocation of BRD1116 to spleens and livers in SCID mice occurred as efficiently as that of BRD691 when inoculated intraperitonally. The ability of BRD1116 to increase the secretion of interleukin-8 following infection of HT-29 epithelial cells was comparable to that of BRD691. Therefore, loss of the HtrA protease in S. typhi does not seem to alter its ability to invade epithelial cells or macrophages or to induce proinflammatory cytokines such as IL-8 but significantly reduces intracellular survival in human intestinal epithelial cells in vitro and in vivo.